Plant-based synthesis of gold and silver nanoparticles using Artocarpus heterophyllus aqueous leaf extract and its anticancer activities - Dewi, Firli RP.; Rohmatika, Aulia U.; Jamil, Arniza KM.; Demircan, Turan; Idris, Muhammad F.; Litazkiyyah, Litazkiyyah; Fahmi, Muhammad; Rosyidah, A'liyatur; Hayati, Alfiah; Sugiharto, Sugiharto (Narra J, 2025)
Green synthesis of nanoparticles has garnered significant attention for its sustainable and environmentally friendly approach. Despite extensive research on Artocarpus heterophyllus-derived nanoparticles using seeds, fruits, and rind, the therapeutic potential of its leaf extract remains largely unexplored, particularly in MCF-7 breast cancer cells. The aim of this study was to investigate the potential of aqueous leaf extract from A. heterophyllus as a reducing and capping agent to synthesize silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs), as well as to evaluate their anticancer efficacy. The nanoparticles were characterized using ultraviolet-visible spectroscopy, transmission electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, and particle size analysis to confirm the formation. To evaluate anticancer potential, key oncogenes associated with cancer proliferation and survival were analyzed, including c-Myc, cyclin D1, human epidermal growth factor receptor-2 (HER-2), microRNA-622 (miR-622), and cyclooxygenase-2 (COX-2). The present study demonstrated that AgNPs and AuNPs synthesized from A. heterophyllus extract had distinct sizes and shapes, with AgNPs averaging approximately 12.75 nm and exhibiting a spherical morphology, while AuNPs averaged 109.26 nm and had a pentagonal shape. Furthermore, AuNPs had no anticancer activity. In contrast, AgNPs showed potent anticancer effects, with inhibitory concentration (IC50) values of 124.626 and 54.981 µg/mL at 48 and 72 hours, respectively. The AgNPs treatment increased the proportion of cells in G2/M phase, indicating the induction of mitotic catastrophe leading to cell death. AgNPs downregulated the expression of several oncogenes associated with cancer cell proliferation and survival (cyclin D1, COX-2, HER-2, and miR622), but did not significantly reduce c-Myc expression. In conclusion, AgNPs derived from A. heterophyllus leaf extract have significant potential as a novel therapeutic agent in cancer treatment while preserving its biocompatibility, emphasizing the promise of sustainable and cost-effective synthesis of plant-based nanoparticles.